Św. abp Józef Bilczewski: biografia językowa i jego wpływ na sytuację językową w Wilamowicach - Król, Tymoteusz (Biografistyka Pedagogiczna, 2022)
Józef Bilczewski (1860-1923), the Archbishop of Lviv, was born in Wilamowice, a small town located on the borderland of Silesia and Lesser Poland, which is inhabited by an ethnic group called Vilamovians. They are the descendants of settlers of Western origin who came to this place in the 13th century. The Germanic Vilamovian language (Wymysorys), which is spoken in Wilamowice to this day, is one of the most important markers of Vilamovian identification. It was the primary language of Bilczewski, at least until he finished primary school. After that, he spoke fluent Polish and German. As a result of later education, Polish became his primary language, and this did not change until the end of his life. The Wymysorys language remained the language of family contact. He must have also had a good command of the German language - he used it as a student, a scholar, and the Metropolitan of Lviv. Bilczewski also had a significant influence on the language situation in Wilamowice. He supported and founded a kindergarten and school, which were to strengthen the position of the Polish language in the community. He was aware of the multilingualism and differentiation of ethnic identification of Vilamovians. He ordered that one of the teachers in kindergarten should know the German language, and that it should be taught as a foreign language in primary school. In this way, he probably won over some of those Vilamovians who, in contrast to him, distanced themselves from Polishness.